Gamete derivation from stem cells: revisiting the concept of genetic parenthood. Issue 11 (20th June 2014) - Mertes, Heidi
Abstract : Genetic parenthood is usually portrayed as a value-neutral concept that can be confirmed or rejected based on objective, scientific tests. However, on inspection, it is exposed as a very complex idea that we might need to consider as something that comes in different shapes and forms and that is open to interpretation rather than being clearly defined and fixed. Different people may therefore also desire different aspects of the general concept of genetic parenthood, which implies that some may not even be satisfied with gametes that have all the properties that their own natural gametes would have, whereas others may be satisfied with a much simpler solution. Encouraging infertility patients to gain insight into what it is exactly that they hope to gain by pursuing genetic parenthood (rather than choosing for donor conception or adoption) may lead them to recognise that the added advantage may be limited and may be acquired in other ways as well. Nevertheless, many people will find it difficult to let go of the desire for genetic parenthood as it is deeply rooted in our genes. Infertility is experienced as a grave medical condition and entails an intense grieving process for many. For that reason alone it is important that the medical and research community develop and apply methods to help people in their quest for genetic parenthood. On the other hand, it is important not to reinforce the dogma that genetic parenthood is 'the best kind of parenthood'.